2017
DOI: 10.1128/genomea.00882-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Lumpy Skin Disease Virus Isolate SERBIA/Bujanovac/2016, Detected during an Outbreak in the Balkan Area

Abstract: The lumpy skin disease virus (LSDV) isolate SERBIA/Bujanovac/2016 consists of 150,661 nucleotides and has a 99.95% nucleotide identity with the Neethling Warmbaths LW strain isolated in South Africa in 1999. This is the first complete LSDV genome determined in Serbia and also in the Balkan area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The modifi cation of VNT in relation to the recommended VNT by OIE [12] refers to the virus used, cell culture and duration of the test. VNT was performed using homologous virus SERBIA/Bujanovac/2016 that originated from LSD clinically infected animal [10,11], and was isolated on MDBK cell line. On the other hand, OIE recommends using Capripoxvirus for VNT [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modifi cation of VNT in relation to the recommended VNT by OIE [12] refers to the virus used, cell culture and duration of the test. VNT was performed using homologous virus SERBIA/Bujanovac/2016 that originated from LSD clinically infected animal [10,11], and was isolated on MDBK cell line. On the other hand, OIE recommends using Capripoxvirus for VNT [12].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated LSDV named SERBIA/Bujanovac/2016 was sequenced in the length of the complete genome and submitted into NCBI GenBank under the number KY702007. Sequencing of the genome revealed that LSDV isolated in Serbia consists of 150661 nucleotides and that it shares 99.95% of nucleotide identity with the Neethling Warmbaths LW strain, which was isolated in South Africa in 1999 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis indicated that the LSDV strain Serbia/Bujanovac/2016 had higher sequence homology with other field LSDV strains (>99.8%) than to vaccine strains (>98.8%). The highest sequence homology of 99.99% was found with field strain Evros/GR/15 (Toplak et al, ). Phylogenetic analysis of whole genome sequences provides more detailed information about genetic differences between the LSDV strains than the phylogenetic analysis based on sequences of only one gene.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated LSDV was completely sequenced (NCBI GenBank, number ) (Toplak et al, ) and compared to available complete genome sequences of field and vaccine lumpy skin disease viruses (LSDV), sheep pox viruses (SPPV) and goat pox viruses (GTPV) obtained from GenBank (http://www.ncbi.nlm.nih.gov). The evolutionary history was inferred using the Neighbour‐Joining method.…”
Section: Methodsmentioning
confidence: 99%
“…In mid-2016, there were reports on the spread of this highly dangerous infectious disease in the Republic of Serbia, which were followed by amendments to the Ordinance on the 2016 Animal Health Protection Program (OGRS, 2016). Emergency vaccination was carried out primarily in Pčinja and Jablanica Districts using the vaccine donated by the European Commission as an aid to Serbia to control and prevent the spread of LSD (OGRS, 2016;Toplak et al, 2017), and later according to the plan in other districts. Apart from the health aspect, the disease has a significant economic impact due to animal production losses (reduced milk production, reduced quality of the skin), restrictions on the movement of susceptible animals and restrictive trade measures which are in force in infected areas (VAMA, 2016a).…”
Section: Introductionmentioning
confidence: 99%